2018
DOI: 10.1038/s41598-018-19198-0
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in bassoon in individuals with familial and sporadic progressive supranuclear palsy-like syndrome

Abstract: Clinical diagnosis of progressive supranuclear palsy (PSP) is sometimes difficult because various phenotypes have been identified. Here, we report a mutation in the bassoon (BSN) gene in a family with PSP-like syndrome. Their clinical features resembled not only those of PSP patients but also those of individuals with multiple system atrophy and Alzheimer’s disease. The neuropathological findings showed a novel three + four repeat tauopathy with pallido-luysio-nigral degeneration and hippocampal sclerosis. Who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 45 publications
0
36
0
Order By: Relevance
“… 21 In mice, BSN deficiency causes early onset severe epilepsy that is 50% lethal in the first 6 months of life. 22 To date, heterozygous BSN variants have been associated with an adult-onset progressive-supranuclear palsy-like syndrome 23 but an autosomal recessive form of this disease has not yet been described.…”
Section: Resultsmentioning
confidence: 99%
“… 21 In mice, BSN deficiency causes early onset severe epilepsy that is 50% lethal in the first 6 months of life. 22 To date, heterozygous BSN variants have been associated with an adult-onset progressive-supranuclear palsy-like syndrome 23 but an autosomal recessive form of this disease has not yet been described.…”
Section: Resultsmentioning
confidence: 99%
“…Bsn-deficient mice display systemic phenotypes including epilepsy and might be also prone to neurodegeneration [ 2 , 13 , 41 , 49 ]. To determine whether increased proteasome activity is a direct result of bassoon deficiency or a secondary effect of systemic phenotypes described in the animals deficient for Bsn expression, we tested chymotrypsin-, trypsin and caspase-like peptidase activities using fluorogenic specific peptidase substrates in cultured cortical neurons derived from newborn Bsn GT animals and their WT littermates.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, mutations in BSN have been linked to human diseases associated with pathological protein aggregation. Bsn mutation found in the patients with familiar PSP-like syndrome significantly decreased the solubility and degradation of Bassoon in heterologous expression system and importantly, led to increased tau aggregation [ 49 ]. Moreover, highly upregulated Bsn expression and its accumulation in large aggregates in the somata of motoneurons, which is a characteristic hallmark of the inflammation-induced degeneration, were found in spinal cord samples from patients with multiple sclerosis (MS) and from the respective disease mouse model, the experimental autoimmune encephalomyelitis (EAE).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although PSP is generally recognized as a sporadic syndrome, there are familial forms of PSP [ 13–15 ] and few pedigrees with PSP-like phenotypes [ 16, 17 ], and a pattern of autosomal dominant inheritance has been proposed [ 14, 15 ]. A case-control study has observed more first-degree relatives with parkinsonism or dementia in patients with PSP than in controls, demonstrating familial aggregation in PSP [ 18 ].…”
Section: Introductionmentioning
confidence: 99%